1963
DOI: 10.1104/pp.38.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Action Spectra of O2 Evolution by Chloroplasts with & without Added Substrate, for Regeneration of O2 Evolving Ability by Far-red, & for O2 Uptake

Abstract: Recent studies (3,6,10,12) have shown that photosynthesis requires two photochemical reactions driven by different pigments. Furthermore, it has been suggested (3, 10, 12) that these two light reactions occur in series. Absorption by chlorophyll b and by chloroplhyll a,7, (so-called accessory pigments) are thought to bring about oxidation of water and evolution of O., with a reduction of an acceptor [X, or perhaps plastoquinone (12)]. A second photochemlical step, mediatefl by a long-wavelength form of chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

1966
1966
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 5 publications
3
18
0
1
Order By: Relevance
“…As a result of these new hypotheses, action spectra were made against a background of monochromatic light. This work showed that at wavelengths of background light, absorbed by biliproteins, the participation of chlorophyll a in the action spectra for red algae could be clearly discerned (Fork 1963a, b), a result anticipated by the work of Blinks (1960a, b, c) who observed similar effects but came to a different conclusion.…”
Section: Larkum and Weyrauch (1977) Also Statedmentioning
confidence: 55%
See 2 more Smart Citations
“…As a result of these new hypotheses, action spectra were made against a background of monochromatic light. This work showed that at wavelengths of background light, absorbed by biliproteins, the participation of chlorophyll a in the action spectra for red algae could be clearly discerned (Fork 1963a, b), a result anticipated by the work of Blinks (1960a, b, c) who observed similar effects but came to a different conclusion.…”
Section: Larkum and Weyrauch (1977) Also Statedmentioning
confidence: 55%
“…His preferred explanation of these effects was in terms of changes in respiration, but these are also explained by two light reactions (see Hill andBendall 1960 andDuysens 1989), and later became important experimental evidence in favor of the hypothesis of two photosystems. Larkum and Weyrauch (1977) further clarified the photosystem I and II in their experimental work on Griffithsia monilis from Athol Wharf in Sidney Harbor which was built on the pioneering work by Fork (1963a, b). In their results, Larkum and Weyrauch stated.…”
Section: Comments By a Series Of Leading Photosynthesis Investigatorsmentioning
confidence: 95%
See 1 more Smart Citation
“…The appearance of an initial oxygen concentration spike has been reported previously, with Fork observing such a effect while investigating oxygen exchange at chloroplasts in solution in the absence of a Hill oxidant, using a macroscale Clark type oxygen electrode. 77 Matsue et al also observed an initial intracellular oxygen spike in algal protoplasts using ultramicroelectrodes with ring radii of approximately 2 µm. 40,41 The oxygen spike was attributed to the consumption of the limited number of, then unknown, electron acceptors by Fork, and to the consumption of the limited number of terminal species (such as NADP) by Matsue.…”
Section: Oxygen Evolution At Chloroplast Filmsmentioning
confidence: 94%
“…Chloroplasts lyophilized for 4 hours shiowed good rates of Hill activiity in the absence of uncouplers. PLANT PHYSIOLOGY tion niot coul)led to photol)hosp)hic)rvl.ationi.One of the I)rol)lems enicounltere(l in the mieasureeent of (., evolutioli by the 14ill reactioni is that of light stimuilated C)., uptake reactionls of the chloroplast suspenlsion (9). The rates of 0., uptake with whole chloroplasts were ustually smnall (ca.…”
mentioning
confidence: 99%